2012
DOI: 10.1103/physrevd.86.127503
|View full text |Cite
|
Sign up to set email alerts
|

Chameleon Brans-Dicke cosmology

Abstract: We consider a generalized Brans-Dicke model in which the scalar field has a potential function and is also allowed to couple non-minimally with the matter sector. We assume a power law form for the potential and the coupling functions as the inputs of the model and show that acceleration of the universe can be realized for a constrained range of exponent of the potential function. We also argue that this accelerating phase is consistent with a large and positive Brans-Dicke parameter. In our analysis, the pote… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 32 publications
3
50
0
Order By: Relevance
“…For instance, at the classical level, equation (34) leads to a modification of the distance luminosity d L because of the energy transfer between the gravitational fields and the electromagnetic field. As an example, for a flat FRLW metric, the new equation reads 2 :…”
Section: Electromagnetic Waves In the Geometric Optic Regimementioning
confidence: 99%
See 1 more Smart Citation
“…For instance, at the classical level, equation (34) leads to a modification of the distance luminosity d L because of the energy transfer between the gravitational fields and the electromagnetic field. As an example, for a flat FRLW metric, the new equation reads 2 :…”
Section: Electromagnetic Waves In the Geometric Optic Regimementioning
confidence: 99%
“…This type of universal gravity/matter coupling has been proposed in order to explain the phenomena usually associated to dark matter (without modifications of the standard model of particles) [1,[26][27][28][29][30], to mimic the cosmological constant [31], to give a reheating scenario in the context of Starobinsky inflation [32], to explain the acceleration of the expansion of the Universe [4,5,19,[33][34][35], to predict (essentially) stable WIMPs [18], or to explain the smallness of the gravitational constant G compared to the proton mass scale [36]. Moreover, it has been shown that under specific assumptions such theories can be compatible with current tight constraints on the equivalence principle(s) (see for instance [10,[37][38][39]).…”
Section: Introductionmentioning
confidence: 99%
“…Usually the chameleon effect is discussed, exclusively, in the Einstein frame formulation of the Brans-Dicke theory, where the scalar field couples directly with the matter degrees of freedom [5][6][7][8][9][10][11][12][13][14][15]. Due to the non-trivial way which the self-interaction potential enters in the KG equation, the discussion of the chameleon effect in the Jordan frame formulation of BD theory seems more obscure than in the Einstein frame.…”
Section: The Chameleon Massmentioning
confidence: 99%
“…Thanks to the chameleon effect [5][6][7][8][9][10][11][12][13][14][15], for instance, it was just recently understood that the experimental bounds on the BD coupling parameter ω bd , which were set up through experiments in the solar system, might not apply in the large cosmological scales if consider BD theory with a potential. According to the chameleon effect, the effective mass of the scalar field m φ , depends on the background energy density of a Electronic address: iquiros@fisica.ugto.mx b Electronic address: rigarcias@ipn.mx c Electronic address: tamegc72@gmail.com d Electronic address: anthort@hotmail.com the environment: In the large cosmological scales where the background energy density is of the order of the critical density ρ crit ∼ 10 −31 g/cm 3 , the effective mass is very small m φ ∼ H 0 ∼ 10 −33 eV, so that the scalar field has impact in the cosmological dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Geometry-matter couplings in the presence of scalar fields were discussed in [10] and the cosmological and astrophysical implications of the f (R, L m ) type gravity theories were investigated in [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. For a recent review of the f (R, L m ) model see [29].…”
Section: Introductionmentioning
confidence: 99%